NEW DESIGNS FOR DUAL BAND ANTENNAS FOR SATELLITE MOBILE COMMUNICATIONS HANDSETS - Daddish, S. M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The design of dual-band antennas for hand-held terminals (HHT) to be used in personal communications via a satellite network (SPCN) is investigated. The quadrifilar helical (QHA) is selected as the optimum design for futher study and new design for a QHA is derived and optimized using a standard Moment-Method program. A dual L-S band design with an input VSWR in its two operating bands of between 1 and 2 was developed, incorporating external shorted turns to achieve the desired passbands. The design of the required hybrid feed phasing network is derived. Experiments with physical realizations of the optimum designs showed good performance and confirmed the computational predictions